Evaluasi Strategi Pemasaran Donat Bomboloni Dalam Menghadapi Persaingan Pasar Kuliner - Abednego Ketaren; Bunga Van Dwi; Desi Khairani; Dwi Jayanti; Dwiva Afrilia; Rakhmawati Purba (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This study aims to evaluate the marketing strategy implemented by the Bomboloni Donut business in facing increasingly tight competition in the culinary market. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation studies of business actors and consumers. The results of the study indicate that the marketing strategies used include the use of social media, price promotions, and product innovation. Although these strategies are able to increase brand awareness and consumer purchasing interest, competition with similar products that offer differentiation and competitive prices remains a major challenge. Therefore, it is necessary to refine the strategy by paying attention to consumer trends, improving product quality, and strengthening brand identity to maintain and increase competitiveness in the dynamic culinary market.